Management of Inorganic Input and Empty Fruit Bunches Towards Efficient Nutrient Use by Young Oil Palm - Wirkom, Evelyn Laika (1999)
The mechanism governing the effect of oil palm EFB on yield have not been thoroughly investigated. Against this background, four experiments were set up; one in the laboratory and three in the field, in an attempt to determine the decomposition pattern of EFB, identify the quality factor(s) controlling EFB decomposition, determine the effect of EFB application on the leaching of N and uptake of N and K fertilisers. Results from the laboratory experiment indicate that, EFB decomposed in 3 distinct phases: viz. an initial immobilisation phase, a later immobilisation phase of reduced intensity and a final re-mineralisation phase. Stalks generally decomposed faster than the spikelets. In the field experiment, the decomposition rates and patterns of EFB component parts were relatively the same as in the laboratory. EFB-lignin, carbon, polyphenol and nitrogen dynamics were evaluated with time and all four-quality parameters showed a strong correlation with soil N dynamics. However EFB-N had a stronger negative (R2 = -0.95) relation (P=O.OI) with soil N dynamics. Application of EFB parts lead to a complete soil N immobilisation for the entire 36 weeks study while EFB tissue N increased with time. Evaluation of leaching of K, Ca, and Mg from EFB, using two sampling methods viz non-destructive sampling (NDS) and destructive sampling (DS) methods, indicated very high loses of K (87 - 88%), Mg (80 - 86%) and Ca (83 - 88%). For all treatments, K was lost at a much faster rate than Mg and Ca. A comparison of the two sampling methods showed that the NDS method was better as it accounted for higher quantities of nutrients leached.